1993
DOI: 10.1524/ract.1993.62.12.55
|View full text |Cite
|
Sign up to set email alerts
|

The Luminescence Spectra of UF4 and UC14

Abstract: Unpolarized luminescence of UC1 4 powder immersed in a silicon matrix was measured at room temperature, at 77 Κ and at 4.2 K. 2S+1 Lj levels were identified assuming D 2 d symmetry for UCI4.. The identification of the observed bands is based on comparison with the results of absorption measurements [5] and with literature data [9,10,11]. Free ion calculations for the tetravalent uranium ion were very helpful [5]. The luminescence of UF 4 as a powder, immersed in a silicon matrix, was also measured and the resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…1a, the energy gap of U 4+ in aqueous solution between 1 S 0 and 3 P 2 levels is so broad (about 17 400 cm −1 ) [7] that the deexcitation process from 1 S 0 may contain luminescence emissions. Moreover, several studies have reported the luminescence properties of U(IV) in solid phases such as U(HPO 4 ) 2 ·nH 2 O powder [6], UF 4 or UCl 4 powder [8], sulfate complexes in a frozen matrix [9] and U 4+ doped LiYF 4 single crystal [10], and the excitation spectra of U(HPO 4 ) 2 ·nH 2 O powder and U 4+ doped LiYF 4 have a characteristic peak in the 240-260 nm range. Based on these considerations, we have carried out spectroscopic experiments on U 4+ in aqueous solutions and discovered the emission spectrum.…”
Section: Introductionmentioning
confidence: 99%
“…1a, the energy gap of U 4+ in aqueous solution between 1 S 0 and 3 P 2 levels is so broad (about 17 400 cm −1 ) [7] that the deexcitation process from 1 S 0 may contain luminescence emissions. Moreover, several studies have reported the luminescence properties of U(IV) in solid phases such as U(HPO 4 ) 2 ·nH 2 O powder [6], UF 4 or UCl 4 powder [8], sulfate complexes in a frozen matrix [9] and U 4+ doped LiYF 4 single crystal [10], and the excitation spectra of U(HPO 4 ) 2 ·nH 2 O powder and U 4+ doped LiYF 4 have a characteristic peak in the 240-260 nm range. Based on these considerations, we have carried out spectroscopic experiments on U 4+ in aqueous solutions and discovered the emission spectrum.…”
Section: Introductionmentioning
confidence: 99%
“…Structural investigations of UF 4 using diffraction methods have extended over the past 75 years. The structure was first reported in 1949, and it was shown that UF 4 crystallized in the C 2/ c space group and was isostructural to MF 4 (M = Th, Np, Pu, Zr, Hf, and Ce) . At this time, the positions of the U atoms were deduced, while those of the F atoms were not determined.…”
Section: Introductionmentioning
confidence: 97%
“…Additionally, UF 4 is envisaged as a fuel for advanced nuclear reactors . The coordination chemistry of UF 4 has been well documented, and the material has been studied in the solid state by spectroscopic (EXAFS, 19 F NMR, , IR, Raman, XPS, absorption, and luminescence), X-ray and neutron powder diffraction (NPD), and theoretical methods . Nevertheless, some physicochemical properties are still not well understood, one of them being the intrinsic negative thermal expansion (NTE) of the material below room temperature .…”
Section: Introductionmentioning
confidence: 99%
“…29 The motivation for studying uranyl difluoride is that the material is relevant to nuclear and safeguard applications (e.g., as an intermediate for UF UO 2 conversion). 32−34 Also, fluorinated U materials (UO 2 F 2 , UF 4 ) exhibit photoluminescent properties 35,36 that are studied to improve radiation detection technology, such as the detection of leaking UF 6 cylinders 37 and sensitive low-dose measurements. 38 Uranium fluoride mr and mp have not yet been reported (vide supra).…”
Section: ■ Introductionmentioning
confidence: 99%
“…Recently, we reported one such approach and prepared uranyl difluoride microspheres from the reaction of UO 3 ms and HF (g) produced from the decomposition of silver bifluoride (SBF) . The motivation for studying uranyl difluoride is that the material is relevant to nuclear and safeguard applications (e.g., as an intermediate for UF 6 and UO 2 conversion). Also, fluorinated U materials (UO 2 F 2 , UF 4 ) exhibit photoluminescent properties , that are studied to improve radiation detection technology, such as the detection of leaking UF 6 cylinders and sensitive low-dose measurements …”
Section: Introductionmentioning
confidence: 99%